Community-level drivers of attitudes towards immigration in Ireland - James Laurence; Frances McGinnity; Keire Murphy (The Economic and Social Research Institute (ESRI), 2024)
International research has shown that community-level characteristics can affect host-country attitudes, in addition to both national-level and individual-level characteristics, and much recent debate in Ireland has centred on challenges communities face in integrating migrants. While we know that Irish attitudes to immigration vary depending on people's personal situation and concerns, the impact of community-level factors has never been explored in Ireland. In this research, we match a 2023 Irish survey on attitudes to immigrants and immigration to small area data on communities from the 2022 census. Drawing on competing theories of group threat and intergroup contact, we examine how community-level factors are associated with attitudes. We find that the proportion of migrants in a community and recent change in that share is not associated with immigration attitudes. However, consistent with international findings, we find that attitudes to immigration are more negative in disadvantaged communities. This is particularly the case in disadvantaged communities where the proportion of migrants has increased since 2011, consistent with theories of intergroup threat. We also find that rural communities tend to be more negative than urban communities on average, but that an increasing proportion of migrants in rural communities has a positive impact on attitudes, to the extent that rural communities with high proportions of migrants show almost no difference in attitudes with urban communities. This is supportive of contact theory. The paper also considers levels of segregation. Higher residential segregation of migrants is associated with more negative attitudes, consistent with previous international research. This may be because of more limited opportunities for contact in segregated communities, or inflated perceptions of the size of migrant communities and the potential threat they pose. Overall, the results imply that it is important to consider the characteristics of communities for understanding attitudes to immigration in Ireland.
Keywords: 330; Einwanderung; Meinung; Gemeinschaft; Segregation; Irland